Educational technology to promote self-efficacy in newborn care: a validation study - Colares Bezerra, Jallyne; Gomes Medeiros Braga, Hévila Ferreira; de Souza Soares, Antônio Marcos; Nascimento da Silva, Maria Jocelane; Jardani de Souza Medeiros, Antônia Ellen; Chaves Rouberte, Emília Soares; Magalhães Monteiro, Flávia Paula; Silva Joventino Melo, Emanuella (Investigación y Educación en Enfermería, 2024)
Objective. To build and validate an educational technology consisting of a flipchart to promote self-efficacy in newborn care. Methods. A methodological study was carried out in two stages: (i) creation of the flipchart and (ii) validation by 25 experts and 50 people who could be the target audience (pregnant women, mothers or family members of newborns). Clarity, language, practical relevance and theoretical relevance were reviewed using the Suitability Assessment of Materials (SAM) instrument. The Content Validity Index and the Flesch Readability Index were calculated. Results. The serial album "Can you take care of your baby" consists of 30 pages. The overall Content Validity Index was 0.93 among experts and 1.0 among the target audience. The flipchart was considered superior quality material, reaching an agreement percentage of 94.9, indicating that it is suitable as an educational technology. Participants suggested adjustments, incorporated into the material for printed production. Conclusions. The flipchart developed and with content validated by experts is suitable for use in health education activities that aim to promote self-efficacy in caring for newborns.